The Analysis of Students’ Errors and Writing Flow in Opinion Paragraphs Written by the First Semester Students of English Department at University of Mataram Academic Year 2024/2025 - Audi Yuliandini; Lalu Thohir; Agus Saputra; Muhammad Amin (Journal of English Education Forum (JEEF), 2026)
This study analyzes grammatical errors and writing flow in opinion paragraphs composed by first-semester students of the English Education Department at the University of Mataram in the 2024/2025 academic year. The primary objectives of this research are to identify the types of errors, investigate the causes of these errors from the students’ perspectives, and evaluate whether the writing flow of the opinion paragraphs meets appropriate standards. Using a mixed-methods approach, data were collected through document analysis of students’ opinion paragraphs and in-depth interviews with purposively selected participants. The findings reveal four major types of errors based on Dulay’s taxonomy: misformation (51.43%), omission (40.00%), misordering (5.71%), and addition (2.86%). These errors are mainly caused by first language (L1) interference, particularly through literal translation from Indonesian into English, as well as carelessness and a lack of self-editing among students. Despite the prevalence of micro-linguistic errors, the students’ writing flow generally demonstrates a sound macro-structural organization. The constructed paragraphs fulfill the criteria of opinion paragraph structure, consisting of a clear topic sentence, relevant supporting details, and a concluding sentence that reinforces the argument. This study is expected to provide insights for educators to focus on students’ areas of weakness in order to improve the accuracy and coherence of their academic writing.